2021
DOI: 10.1101/gad.348221.120
|View full text |Cite
|
Sign up to set email alerts
|

WWTR1(TAZ)-CAMTA1 reprograms endothelial cells to drive epithelioid hemangioendothelioma

Abstract: Epithelioid hemangioendothelioma (EHE) is a poorly understood and devastating vascular cancer. Sequencing of EHE has revealed a unique gene fusion between the Hippo pathway nuclear effector TAZ (WWTR1) and the brain-enriched transcription factor CAMTA1 in ∼90% of cases. However, it remains unclear whether the TAZ-CAMTA1 gene fusion is a driver of EHE, and potential targeted therapies are unknown. Here, we show that TAZ-CAMTA1 expression in endothelial cells is sufficient to drive the formation of vascular tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 57 publications
3
39
0
Order By: Relevance
“…Findings from our study are consistent with recent reports that demonstrate a crucial role for TAZ in cancers. For example, the fusion of the TAZ gene with the gene that encodes CAMTA1 transcription factor is responsible for the majority of cases documenting a rare tumor known as Epithelioid Hemangio-Endothelioma (EHE) that primarily affects soft tissues, including lung [ 57 , 58 ]. Altogether, our findings highlight the important function of SFTA1P in a TAZ-dependent regulation of Hippo-YAP/TAZ signaling and NSCLC tumorigenesis, which warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our study are consistent with recent reports that demonstrate a crucial role for TAZ in cancers. For example, the fusion of the TAZ gene with the gene that encodes CAMTA1 transcription factor is responsible for the majority of cases documenting a rare tumor known as Epithelioid Hemangio-Endothelioma (EHE) that primarily affects soft tissues, including lung [ 57 , 58 ]. Altogether, our findings highlight the important function of SFTA1P in a TAZ-dependent regulation of Hippo-YAP/TAZ signaling and NSCLC tumorigenesis, which warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, Driskill et al generated an overexpression system for TC expression based on a Tet-Off approach [ 92 ]. Concordant with the findings of Seavey et al, this study demonstrated that TC expression is lethal during embryogenesis.…”
Section: Novel Model Systems For Studying Ehe Biologymentioning
confidence: 99%
“…If the TC fusion protein is controlled by these regulators, the action of TC could be diminished, either by the inhibition of the negative regulators of the Hippo pathway, or by positive regulators of TC. Despite the initial suggestion that TC is unregulated by the Hippo pathway, recent evidence suggests that Hippo alters the action of TC [ 92 ]. In unpublished work, via co-immunoprecipitation followed by mass spectrometry, we have seen that the TC protein is phosphorylated at the regulatory S89 residue and that it associates with the 14-3-3 protein [ 97 ].…”
Section: Development Of Targeted Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several previous reports have demonstrated the roles of YAP [ 10 , 11 , 12 , 13 , 14 , 15 ] and TAZ [ 16 , 17 , 18 ] in mature endothelial cells and the angiogenic process. Even though YAP and TAZ possess less than 60% amino acid sequence similarity, they are often considered to control the same group of target genes and have similar functions [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%